Konsep Pemikiran Ibn Taymiyah Tentang Kepemimpinan Politik Dalam Islam - Moch. Azis Qoharuddin (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2019)
Abstract Ibn Taymiyah's thoughts on political leadership in Islam include the form of leadership, the requirements of a leader, and the electoral procedures of the leader. Also Besides, what are the differences and similarities and the advantages and disadvantages of political leadership from the viewpoint of political philosophy?. The research data is compiled through text reading and study (text reading) and subsequently analyzed by the approach of political philosophy, descriptive method, comparative and content analysis. The results of the study concluded in Ibn Taymiyah's thought, leadership forms tended to maintain the status quo of the autocracy kingdom, the requirements of the leader were people who had strengths (quwwah) and Integrity (trust), and leaders Elected or shadowed by Ahl-Shawkah, but it does not explain in detail how the institution was formed and how it was chosen. Ibn Taymiyah did not use the term imamate or caliphate in leadership, not requiring the leader to be of the tribe of Quraish, emphasized the importance of deliberation and alluded to the figure of Fir'aun and Qarun as the disgraceful man. Ibn Taymiyah's thought lies in the guidance to elect state officials, there should be a harmony between the leader and his deputy, the terms of strength (quwwah) and Integrity (trust), these terms are the same as that of Plato, the self-control, wisdom, courage, and justice.